1994
DOI: 10.1210/jcem.79.3.7521354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin on the hepatic production of insulin-like growth factor-binding protein-1 (IGFBP-1), IGFBP-3, and IGF-I in insulin-dependent diabetes.

Abstract: Insulin-like growth factors (IGFs) circulate attached to binding proteins (IGFBPs). Only the unbound form of IGF is suggested to be biological active. The main source of circulating IGF-I and IGFBP-1 is considered to be the liver, but that of circulating IGFBP-3 is not known. IGF-I and IGFBP-3 are GH dependent, whereas IGFBP-1 is insulin regulated. The aim of the present study was to examine the effect of insulin on the hepatic secretion of IGFBP-1, IGFBP-3, and IGF-I. Seven insulin-dependent diabetic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
199
1
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(222 citation statements)
references
References 10 publications
20
199
1
2
Order By: Relevance
“…Although glucose is not a direct stimulator of IGFs in postnatal life, insulin has been shown to stimulate IGF-I production in adults [28]. The present study revealed a positive correlation between umbilical IGF-II levels and placental weight in diabetic pregnancy.…”
Section: Relation Between Birth Weight and Serum Concentrations Of Fesupporting
confidence: 48%
See 1 more Smart Citation
“…Although glucose is not a direct stimulator of IGFs in postnatal life, insulin has been shown to stimulate IGF-I production in adults [28]. The present study revealed a positive correlation between umbilical IGF-II levels and placental weight in diabetic pregnancy.…”
Section: Relation Between Birth Weight and Serum Concentrations Of Fesupporting
confidence: 48%
“…In addition, we found that they were significantly higher in IDDM mothers and their infants. Recent studies have shown that serum IGFBP-1 levels are, at least in part, regulated by insulin [28,37,38]. The higher maternal values in IDDM may represent a deficiency of insulin action.…”
Section: Relation Between Birth Weight and Serum Concentrations Of Fementioning
confidence: 99%
“…32 Insulin is the principal regulator of IGFBP-1 and is reported to inhibit hepatic IGFBP-1 synthesis. 33 Because of this property, IGFBP-1 is thought to play an important role in the regulation of IGF bioactivity. Therefore, the obesityrelated hyperinsulinaemia may decrease circulating concentrations of IGFBP-1, which can result in elevated free IGF-1 in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Another considerable proportion of changes in net protein balance was accounted for by the decrease in IGFBP-1 after rhGH. This protein is produced by the liver and both insulin (42) and rhGH (41) reduces IGFBP-1 levels, thus increasing the bioavailability of IGF-I.…”
Section: Discussionmentioning
confidence: 99%